2022
DOI: 10.1016/j.psyneuen.2021.105623
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between prenatal testosterone and autistic traits in adolescents?

Abstract: Prenatal testosterone (pT) is a crucial component in physiological masculinization in humans. In line with the Prenatal Sex Steroid Theory of autism, some studies have found a positive correlation between pT and autistic traits in childhood. However, effects in adolescence have not been explored. Hormonal and environmental changes occurring during puberty may alter the strength or the nature of prenatal effects on autistic traits. The current study examines if pT relates to autistic traits in a non-clinical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 106 publications
0
12
1
Order By: Relevance
“…On the surface, these results do not appear to align with a recent study comparing prenatal testosterone (pT) to autistic traits in adolescents and young adults aged 13 to 21 [68]. Similar to our current report, there were no direct associations between pT and autistic traits.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…On the surface, these results do not appear to align with a recent study comparing prenatal testosterone (pT) to autistic traits in adolescents and young adults aged 13 to 21 [68]. Similar to our current report, there were no direct associations between pT and autistic traits.…”
Section: Discussioncontrasting
confidence: 93%
“…Earlier pubertal timing was also observed in males with ASD albeit during middle adolescence [70]}, which again seems to align with the rise in testosterone in males. Despite this intriguing connection between pubertal testosterone, autism, and sex, there are notable differences in methods between the current study and Dooley et al (2022), which include: sample differences (confirmed ASD diagnosis vs. self/parent-report of autistic traits), sample age (10-13 years vs. 13-21 years), testosterone effects (pubertal/activational vs. prenatal/organizational), and pubertal development (Physical Exam Tanner staging vs. PDS questionnaire), respectively. Furthermore, while the current study did not find any relationship between ASD diagnosis and testosterone at varying developmental stages, we did not explore differences according to early-, normative-, or late-pubertal timing, nor did we examine a relationship with age of menarche in females.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A second theoretical perspective is the neurohormonal hypothesis, which posits that prenatal androgen exposure organizes parts of the brain (in terms of structure (23) and function (24)) as well as sex-differentiated psychological and behavioral characteristics (25), including gender identity and sexual orientation. The surge in sex hormones during adolescence is argued to influence parts of the brain to be further expressed in a relatively male-or female-typical manner, based on the earlier prenatal brain organization (6)(7)(8)(9)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%